New 13X zeolite for propylene/propane separation by vacuum swing adsorption - M. C. Campo (2013)
Adsorption equilibrium isotherms for propane and propylene on a new 13X zeolite from CECA were measured at three temperatures (323, 373, 423 K) up to 5 bar. Maximum capacities of 3.47 and 3.08 mol/kg were found for propylene and propane, respectively. These values are significantly higher than those reported in literature. Adsorption isotherms were fitted with Toth equation. Heats of adsorption were calculated as a function of loading from experimental data with Van't Hoff equation leading to 53 kJ/mol and 35 kJ/mol for propylene and propane, respectively; values were also obtained from fitting with Toth equation. Single and binary breakthrough curves were measured and simulated with a mathematical model for fixed bed adsorbers. A 5-step VSA cycle was also simulated to produce 99.5% propylene from a 25:75 propane/propylene mixture; experimental validation confirms a good prediction. Propylene was obtained with a purity of 99.54%, a recovery of 85% and a productivity of 1.46 mol(C3H6)/kg(ads)/h.